Peran Konektivisme Dalam Pembelajaran Digital - Timoteus Ajito (Journal on Education, 2024)
The aim of this research is to find out how connectivism theory is implemented in digital learning. The research method used is qualitative with a library research approach (library study). Data were obtained from relevant information repositories, including scientific texts, periodicals, and academic journals that investigate the subject of inquiry. The data analysis process involves the systematic organization of information, deconstructing it into discrete components, integrating it into a cohesive framework, identifying salient elements for further examination, and deriving conclusions that are understandable to the scientific community. The results obtained show that the implementation of connectivism offers diversity of learning through various networks, helping new generations collaborate to find solutions to the increasing number of questions. Although the theory presented by George Siemens and Stephen Downes is important and valid, this theory is a tool used in the learning process for instruction or curriculum, not a stand-alone learning theory, but connectivism requires a combination of learning theory and digital technology as a learning medium. The theory also forces educators to look at what is being done in digital education, rethink what is happening, and philosophize about how each piece fits together. Continuously evaluating how each new generation learns about instruction and curriculum serves to keep education at a high standard. An educational system that is adaptive and responsive to these changes is essential to ensure that teaching methods remain relevant and effective in facing modern-day challenges. Thus, the role of technology in education is not only as a tool, but also as the main driver that drives innovation and transformation in the way we educate future generations.